2016
DOI: 10.1007/s11606-016-3645-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: A Narrative Review Examining the Evidence for Ten Beliefs

Abstract: Over the past decade, a large body of observational evidence has suggested an association between lower vitamin D status (25-hydroxyvitamin D) and multiple acute and chronic disorders, including cancer, multiple sclerosis, depression and respiratory tract infections. This evidence has fostered the hypothesis that increasing vitamin D intake may treat and prevent such disorders. Our objective was to perform a critical analysis of the highestlevel evidence for ten common beliefs regarding vitamin D for the preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 76 publications
4
26
1
1
Order By: Relevance
“…1 However, we disagree with their conclusions that the current literature supports only a beneficial effect of vitamin D supplementation on fracture risk. As the authors correctly point out, observational studies of vitamin D are subject to important limitations since, in general, a decreased level of vitamin D is a marker of poor health.…”
Section: T O the Editorcontrasting
confidence: 63%
“…1 However, we disagree with their conclusions that the current literature supports only a beneficial effect of vitamin D supplementation on fracture risk. As the authors correctly point out, observational studies of vitamin D are subject to important limitations since, in general, a decreased level of vitamin D is a marker of poor health.…”
Section: T O the Editorcontrasting
confidence: 63%
“…5 Regarding respiratory tract infection clinical trials (Belief 3 in Ref. 1), it is noted that in the trial from New Zealand finding no benefit for large-dose vitamin D 3 , the baseline 25(OH)D concentration was 72.5 nmol/l, which is in stark contrast to the trial from Mongolia finding significant benefits of 300 IU/day vitamin D 3 had a baseline concentration of 17.5 nmol/l.…”
Section: T O the Editormentioning
confidence: 97%
“…1 What the authors failed to realize is that many of the clinical trials were based on the guidelines for pharmaceutical drugs. Such trials have two main assumptions: (1) that the trial is the only source of the agent and (2) that there is a linear doseresponse relation.…”
Section: T O the Editormentioning
confidence: 99%
“…2 Third, to support the belief that individuals with lower serum levels are more likely to reap benefits from vitamin supplementation, Dr. Grant references a single study that demonstrated infection prevention with supplementation for those with low Vitamin D levels. We too had raised this potential important linkage in our paper, 1 but noted the results cannot be applied to all developing countries. A large trial in Kabul Afghanistan did not see any reduction in pneumonia when infants were provided with vitamin D supplementation, despite vitamin D levels being roughly 50 nmol/L or higher in the treated arm, while levels in the untreated arm were lower by roughly 20 nmol/L or more at most time points (Vitamin D levels estimated from Fig.…”
mentioning
confidence: 88%
“…1 However, this evidence is observational and any potential benefits resulting from Vitamin D supplementation are only an extrapolation from this lower-level evidence. Unfortunately, a cancer benefit from Vitamin D supplements is not supported by the available higher-level evidence, which suggests future research on cancer mortality is unlikely to yield meaningful change in the estimate of no effect.…”
mentioning
confidence: 99%